Generative AI, Its Use and People’s Interest: Comparison of First Three Months and Implications to Its Future in East Asia - HUA, Jinling; SHIRATSUCHI, Yuka; SHAW, Rajib (Journal of Ecohumanism, 2025)
Role and importance of Generative Artificial Intelligence (GAI) are now well recognized. Starting from 2014, the GAI has evolved strongly over past ten years, and a good data set helps it to be more robust, as well as popularize it with wider users. After its launch in November 2022, ChatGPT has drawn global attention. In this paper, the analysis covers the submissions related to ChatGPT during the three-month period from 1st of December 2022 to 28th of February 2023 in three East Asian Countries: China, Japan and Korea. There is differential momentum of number of users in the studied countries, which are attributed to role of media and governance system in popularizing ChatGPT. Analysis shows certain level of commonalities in the interest of the users. Technology is possibly the common interest area in all three countries. Chinese users are more interested in innovation, while Korean and Japanese users were more interested in business. Japanese users also showed interest in entertainment. Keeping the current growth and future potentials of GAI, the paper also discusses the importance of ethical dimension of use of GAI, especially on its role in mis- and dis-information. People’s awareness and governance mechanism are also very critical for appropriate use of GAI in future.